Nonclinical safety and pharmacokinetics of Miglyol 812: A medium chain triglyceride in exenatide once weekly suspension. Issue 10 (28th May 2018) - Buss, Nicholas; Ryan, Patricia; Baughman, Todd; Roy, Denis; Patterson, Claire; Gordon, Carolyn; Dixit, Rakesh
Abstract: Exenatide, a glucagon‐like peptide‐1 receptor agonist was originally developed as either a twice daily or once weekly injectable therapeutic for patients with type 2 diabetes. Exenatide QW suspension was developed for use with an autoinjector device, in which the microspheres are suspended in Miglyol 812, a mixture of medium chain triglycerides (MCTs). MCTs are a class of lipids whose fatty acid chains contain from six to 12 carbon atoms (medium chain fatty acids or MCFAs). While MCTs are edible oils present in many foods, including foodstuffs containing coconut and palm kernel oils, limited information is available regarding the oral and subcutaneous bioavailability of MCTs as well as safety following subcutaneous injection. These studies were designed to investigate the non‐clinical pharmacokinetics and safety of MCTs. In a single dose pharmacokinetic study, MCFAs were rapidly detected in the plasma of rats following oral administration of either Miglyol 812 or tricaprylin at doses of 10 or 9.48 g kg −1, respectively. Following subcutaneous dosing with Miglyol 812, MCFAs were rapidly absorbed with a similar profile to that following oral dosing. Furthermore, the toxicity of Miglyol 812 alone was evaluated in a 3 month repeat dose toxicology studies in cynomolgus monkeys. In this study, weekly subcutaneous doses of 0.15 g kg −1 did not elicit any treatment‐related effects in cynomolgus monkeys. In conclusion, these studies alongside the available literature data show that Miglyol 812 is a safe excipient for use in subcutaneously administered therapeutics. Abstract : Exenatide QW suspension, a glucagon‐like peptide‐1 receptor agonist, was developed for use with an autoinjector device, which included Miglyol 812, a mixture of medium chain triglycerides. Non‐clinical studies conducted to characterize the pharmacokinetics and toxicity of Miglyol 812 showed that medium chain triglycerides were both orally and subcutaneously bioavailable in rats and that there were no adverse findings following repeated weekly dosing of Miglyol 812 to cynomolgus monkeys for 3 months at 0.15 g kg −1 .